'Figuring it out'. Continuity or discontinuity of work in young rural-urban migrants' education to work transition in Kathmandu, Nepal. (21st April 2023) - Basnet, Neha; Timmerman, Margaretha C.; van der Linden, Josje
ABSTRACT: Although youth research has highlighted the importance of a holistic understanding of the changing nature of youth education to work transitions, few studies have examined these transitions from a process perspective. In this study on continuity and discontinuity of work, the process perspective proved to be useful to analyse the education to work transition of rural-urban migrants in Kathmandu, Nepal. Qualitative longitudinal data, consisting of two consecutive in-depth interviews, with twenty-one participants, reveal how they shift choices, negotiate positions, embrace changes and decisions. A reemphasis on the understanding of rural-urban migrant youth education to work transition as part of a process is suggested calling for a holistic understanding of rural-urban migrant youth education to work transition among scholars and policymakers in Nepal and also in other contexts.